CLT at the Higher Secondary Level in Bangladesh: Theory and Practice - Ullah, Md Mohib (IIUC Studies, 2016)
With the progress of time, the aim of teaching and learning English as a Second Language (ESL) or English as a Foreign Language (EFL) changed, and so did the approaches and methods in language teaching. Different methods and approaches emerged and were replaced, influenced or contributed to the emergence of new methods. It is widely acknowledged that one umbrella approach to language teaching that has become the accepted "norm" in this field is the Communicative Language Teaching Approach. This study deals with the theories and practices of CLT at the Higher Secondary level in Bangladesh. Realizing the significance of CLT, The Ministry of Education in Bangladesh made groundbreaking attempts to implement CLT in the new context and also brought some changes in the curriculum in 1990s. Along with attempting to provide a real picture of how CLT is practiced and utilized in an ESL/EFL context, this study focuses on the Practice of CLT approach in Bangladesh. Moreover, this study intends to propose some propositions to be implemented for better practice of CLT in ESL/EFL contexts. IIUC Studies Vol.12 December 2015: 71-86